Model-Based Estimation of Congestion-Related Travel Time Losses on Freeways. Issue 1 (January 2014) - Geistefeldt, Justin; Hohmann, Sandra
For economic assessment of road infrastructure investments and evaluation of operational strategies, estimation of travel times is of particular importance. This paper introduces a two-component model to estimate total or average travel times on freeways. The model differentiates between travel times in fluid traffic conditions, which depend on the length of the segment, and congestion-related travel time losses, which depend only on the volume-to-capacity ratio of the bottleneck. On the basis of traffic data from 50 freeway sections in Germany, the total travel time losses from congestion occurring in 1 year are estimated by macroscopic simulation. With the simulation model, the travel time losses can be related to the volume-to-capacity ratio of the hour in which the congestion was caused. A model function was developed to represent the congestion-related travel time losses in relation to the volume-to-capacity ratio. The application of the model for the assessment of operational strategies is demonstrated for the example of hard-shoulder running on freeways.